2015
DOI: 10.1016/j.bjoms.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Up to a quarter of patients with osteonecrosis of the jaw associated with antiresorptive agents remain undiagnosed

Abstract: Recent data suggest that the traditional definition of bisphosphonate-associated osteonecrosis of the jaw (ONJ) may exclude patients who present with the non-exposed variant of the condition. To test the hypothesis that a proportion of patients with ONJ remain undiagnosed because their symptoms do not conform to the traditional case definition, we did a secondary analysis of data from MISSION (Multicentre study on phenotype, definition and classification of osteonecrosis of the jaws associated with bisphosphon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 24 publications
1
85
0
12
Order By: Relevance
“…As 20-30% of ONJ cases escape the classical definition (requiring 8-week lasting bone exposure), [24,35,36] great attention should be paid to imaging studies (particularly by CT or bone scan scintigraphy) in order to avoid underestimation of MRONJ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As 20-30% of ONJ cases escape the classical definition (requiring 8-week lasting bone exposure), [24,35,36] great attention should be paid to imaging studies (particularly by CT or bone scan scintigraphy) in order to avoid underestimation of MRONJ.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the purely clinical-based definition of ONJ is questioned by the emergent role of imaging studies. [35,36] 3. ONJ related to drugs other than antiresorptives Between 2003 and 2008, the medical literature registered an explosion of Reports and Papers regarding ONJ related to BPs, the so-called BRONJ.…”
Section: Definition Of Onjmentioning
confidence: 99%
“…Non-exposed BRONJ has been associated with oral bisphosphonates, 16,23 osteoporosis, odontogenic infections, 23 tooth extraction and prosthetic appliances 16 ( Table 2). Schiodt et al 20 reported tooth extraction prior to BRONJ in 79% of patients with non-exposed lesions.…”
Section: Management Of Patientsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20] Since then, two updates have been performed by the AAOMS 21,22 and several authors have discussed the possibility of BRONJ occurrence despite the absence of bone exposure. 16,18,20,23,24 According to them, this condition should be called nonexposed BRONJ. 18,20,24 BRONJ is a relatively recent entity and many doubts regarding its aetiopathogenesis and approach still persist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation